2020
DOI: 10.1002/hed.26389
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology, surgical management, and impact of margins in skull and mandibular osseous‐site tumors

Abstract: The aim of the study was to characterize the epidemiology and treatment outcomes of head and neck (HN) osseous-site tumors. Methods: Descriptive analyses and multivariate Cox regressions were performed to analyze the effect of surgery on overall survival (OS) utilizing the National Cancer Database (2004-2016). Results: Of 2449 tumors, surgery was utilized in 84.5% of cases. OS was worse in osteosarcoma (5-year OS: 53.4% [SE: 2.5%]) compared with cartilage tumors (5-year OS: 84.6% [SE: 1.8%]) (log-rank P < .001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In this context, Krishnamurthy et al found positive resection margins as the single important prognostic factor affecting patient survival (14). Although this study contained only 14 patients, Torabi et al analysed a cohort of 2449 osseous tumors of the head and neck region and confirmed association of positive resection margins with decreased OS in the osteosarcoma subgroup (15). These findings underline that effective ablative surgery represents the main therapeutic principle in MOS.…”
Section: Discussionmentioning
confidence: 72%
“…In this context, Krishnamurthy et al found positive resection margins as the single important prognostic factor affecting patient survival (14). Although this study contained only 14 patients, Torabi et al analysed a cohort of 2449 osseous tumors of the head and neck region and confirmed association of positive resection margins with decreased OS in the osteosarcoma subgroup (15). These findings underline that effective ablative surgery represents the main therapeutic principle in MOS.…”
Section: Discussionmentioning
confidence: 72%
“…The use of negative margin status as a surrogate marker for total resection has previously been utilized in analyses of esthesioneuroblastoma, sinonasal mucosal melanoma, osseous-based skull and mandibular tumors, and skull base chondrosarcoma. 9 10 11 12 Clinical covariates included age (<65 or ≥65 years), sex, race (Caucasian, African American, other), presence of comorbidities, year of diagnosis (2004–2009 or 2010–2015), AJCC Analytic Stage (1–2 or 3–4), nodal involvement, metastatic involvement, histology (unspecified, chondroid, or dedifferentiated), and tumor size (<5 or ≥5 cm). Sociodemographic covariates included facility type (academic or nonacademic) and location (east, central, or west), insurance status (private, government, or uninsured), income quartile (<$48,000 or ≥$48,000), education level of residence (<13% or ≥13% without a high school diploma), population size (<250,000 or ≥250,000 individuals), and distance from provider to patient.…”
Section: Methodsmentioning
confidence: 99%
“…The use of negative margin status as a surrogate marker for total resection has previously been utilized in analyses of esthesioneuroblastoma, sinonasal mucosal melanoma, osseous-based skull and mandibular tumors, and skull base chondrosarcoma. [9][10][11][12] Clinical covariates included age (<65 or ≥65 years), sex, race (Caucasian, African American, Other), presence of comorbidities, year of diagnosis (2004-2009 or 2010-2015), AJCC Analytic Stage (1-2 or 3-4), nodal involvement, metastatic involvement, histology (unspecified, chondroid, or dedifferentiated), and tumor size (<5 or ≥5 cm). Sociodemographic covariates…”
Section: Accepted Manuscriptmentioning
confidence: 99%